Microcredentials – Potential, limitations and applicability of the concept in labour-marketrelated vocational education and training systems : Expert Opinion - Stolte, Harry [Verfasser]; Spöttl, Georg [Verfasser] (Bundesinstitut für Berufsbildung, 2025)
"Microcredentials are gaining relevance in the context of lifelong learning and the flexibilisation of educational pathways. Against this background, this expert opinion examines the extent to which the concept of microcredentials – as defined in the 2022 EU Council Recommendation – can be transferred to workplace related VET systems. The results reveal fundamental areas of tension: the work process-oriented logic of dual VET is only compatible with the modular, small-scale approach of microcredentials to a limited extent. Particular challenges arise in the areas of competence orientation, quality assurance and recognition practices. While the EU Council Recommendation emphasises microcredentials as a tool for promoting mobility and lifelong learning, the study reveals serious systemic resistance and considerable implementation hurdles for the vocational training sector. The structural differences between small-scale learning opportunities and vocational training logic lead to conflicting goals – especially between the desired flexibility and the preservation of established quality standards in vocational training. The study warns against uncritical adoption of the concept, as this could jeopardise proven dual training structures and lead to a decline in quality, and calls on stakeholders involved in the issue to take greater account of the specific requirements of in-company training. The study is intended to stimulate a differentiated discussion on the possibilities and limitations of microcredentials in dual systems, without making any hasty recommendations for implementation."
Keywords: S 1 Stufen der Berufsbildung; L 4.2.3 Internetbasiertes Lernen / E-Learning; S 1.5 Weiterbildung; S 1.3.5 Zusatzqualifikation; S 2.3 Berufsbildungspolitik; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; 370; Berufsbildung; E-Learning; Lehrgang; Zusatzqualifikation; Lebenslanges Lernen; EU-Bildungspolitik